TRENDS OF THE DEVELOPMENT OF HIGHER PHARMACEUTICAL EDUCATION - Natalia S. Golikova; Vadim V. Tarasov; Ivan I. Krasnyuk; Elena F. Savosina (Высшее образование в России)
The dynamic development of the pharmaceutical industry in the Russian Federation is closely connected with training of qualified personnel, which in turn requires modernization of the education programs of higher professional education. Comparative analysis of the field, objects and kinds of professional activity, professional tasks of the pharmacist presented in the current Federal state educational standard (FSES HPE 3) and the new FSES HE 3+ in the specialty «pharmacy» allows to identify the main patterns and trends in the development of the Russian pharmaceutical education. Educational programs developed and implemented by institutions of higher vocational education must meet the requirements of employers for graduates with regard to the transfer of the domestic pharmaceutical industry to international standards.